2013
DOI: 10.1002/gps.3968
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression and maintenance medication adherence among Medicare beneficiaries with chronic obstructive pulmonary disease

Abstract: Objective Depression is a significant comorbidity in patients with chronic obstructive pulmonary disease (COPD). Although comorbid depression is associated with low use and poor adherence to medications treating other chronic conditions, evidence of the relationship between depression and COPD management is limited. This study estimated the association between depression and COPD maintenance medication (MM) adherence among patients with COPD. Methods This cross-sectional study used a 5% random sample of 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 37 publications
4
61
1
3
Order By: Relevance
“…Our results suggest that individuals with more than three chronic conditions are at highest risk of poor adherence. This effect was mitigated by increased severity of COPD symptoms, evidenced by acute inhaler use, oxygen use, and COPD-related hospitalizations, and is consistent with a prior report (30). Historically, use of and adherence to COPD maintenance medications has been suboptimal, with many individuals with COPD not receiving any maintenance medications (14,15,17).…”
Section: Original Researchsupporting
confidence: 83%
See 3 more Smart Citations
“…Our results suggest that individuals with more than three chronic conditions are at highest risk of poor adherence. This effect was mitigated by increased severity of COPD symptoms, evidenced by acute inhaler use, oxygen use, and COPD-related hospitalizations, and is consistent with a prior report (30). Historically, use of and adherence to COPD maintenance medications has been suboptimal, with many individuals with COPD not receiving any maintenance medications (14,15,17).…”
Section: Original Researchsupporting
confidence: 83%
“…Qian and colleagues analyzed maintenance medication adherence, using a crosssectional study design, among Medicare beneficiaries with COPD and reported that individuals with depression were 11% less likely to have high adherence (30). Our study overcame the limitations of the crosssectional study design by examining the longitudinal association between depression and medication adherence, yet reported results consistent with those of the study by Qian and colleagues (9% less likely to have greater adherence).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Previous studies have linked psychological comorbidities with increased risk of mortality in patients with COPD, although data about readmissions are less definitive (38,41). Coventry and colleagues prospectively examined psychosocial risk factors, including depressive symptoms and social support, and readmissions in a small cohort of patients with COPD in the United Kingdom and found a modest correlation with readmission risk in 1 year (26).…”
Section: Original Researchmentioning
confidence: 99%